SOME ASPECTS GEOGRAPHICAL - HISTORICALLY THINKING IN THE CONTEXT OF THE TIME: REVIEW OF LITERATURE - Rajović, Goran; Bulatović, Jelisavka (REVISTA GEOGRÁFICA ACADÊMICA, 2020)
The main objective of this paper confirm the importance understanding that are historical events and geographical factors in interdependence, that everything that relates with human population and vital for it takes place the geographical area that are a key factor in historical events organization and transformation of space. Acording to Komušanac and Šterc (2011) "one of the basic problems of theoretical considerations historical geography from its beginnings as an independent discipline was unclear positioning of its subject - content base and defining its limits within the frame of the system of scientific geography. Theoretic analysis of historical and geographical aspects of research is determined by the historical - geographic factors, and their interactive relationship is set as a prerequisite for the understanding of objective reality and the spacious design and prediction of relations in the space-time continuum". After analyzing relationships of main of geography fields with other sciences and Venn diagram of the relations of geography history and their subject matter with of the four principal discourses of geography, a review of the theoretical considerations and synthesis of the research results, confirmed by the general geographical, and defined the specific historical and geographical principles as the integrative connection between natural and social science system. Historical geography is therefore the geography of the past particularly in the sense that it studies this past in order to understand the present and therefore strives also for the practical application of its findings.